MATERNIDADE NEGRA: Um diálogo entre Carolina e Nnu Ego - FARIAS, Ednólia da Silva (2024)
The aim of this dissertation was to analyze the representations of motherhood in the novels The joys of matherhood (2018), by Buchi Emecheta and in Quarto de Despejo: Diário de uma Favelada (2020), by Carolina Maria de Jesus from the perspective of Comparative Literature and Cultural Studies approaches. In this sense, this research also represented a place to understand the performances and subjectivities of black mothers portrayed in the literary universe and social formation through historical and cartographic elements. Regarding methodology, we applied theories on topics such as: identity, motherhood, black women, providers, by Gonzalez (2020), hooks (2019), Bhabha (1999), Hall (2006), among others. The method used in the analyzes was both hermeneutic and comparative in nature and was understood from a close reading of the theoretical and literary texts selected in this study. The themes present inboth literary works intertwine as they raise questions about patriarchal culture, poverty, child labor, physical and psychological freedom through education, women's independence, and especially motherhood. Buchi Emecheta presents us with a prototype of what it means to be a colonized woman, in which they are always motherhood prisoners because before becoming a mother properly there is the desire, and when one becomes a mother, comes the responsibility. Carolina Maria de Jesus presents us with the portrayal of a woman who suffers from all kinds of symbolic violence and prejudice besides to her life being dictated by the choices she makes, the biggest of which is being a single mother. In this sense, the analyzes suggest the existence of a stereotypical view of black mothers and a new category of these women's bodies, namely the maternal body, even if some researchers claim that their behavior is defined by the subordinate body, therefore, women moved by a unique feeling - being a mother and protecting their children even if they become unpopular in society and among their offspring.